2019
DOI: 10.3389/fonc.2019.00536
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging Reveals Microstructural Heterogeneity of Normal-Appearing White Matter and Related Cognitive Dysfunction in Glioma Patients

Abstract: Immunohistochemical data based on isocitrate–dehydrogenase (IDH) mutation status have redefined glioma as a whole-brain disease, while occult tumor cell invasion along white matter fibers is inapparent in conventional magnetic resonance imaging (MRI). The functional and prognostic impact of focal glioma may however relate to the extent of white matter involvement. We used diffusion tensor imaging (DTI) to investigate microstructural characteristics of whole-brain normal-appearing white matter (NAWM) in relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 52 publications
2
34
0
Order By: Relevance
“…Up to now, there have been many reports on ADC histogram in grading glioma, most of which are about the application of texture analysis in heterogeneity of tumors [14][15][16][17]. However, there are few reports about the use of texture analysis in ependymoma grading [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, there have been many reports on ADC histogram in grading glioma, most of which are about the application of texture analysis in heterogeneity of tumors [14][15][16][17]. However, there are few reports about the use of texture analysis in ependymoma grading [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…IDH-mutation status, which represents slower local tumor growth rates and the less-infiltrative nature of diffuse tumor cell migration, has emerged as a major prognostic molecular marker in glioma patients [36][37][38][39]. Using DTI analysis, microstructural alterations in white matter distant from the tumor location in IDHwildtype glioma patients compared with IDH-mutated glioma patients were observed, which may be attribute to tumor cell invasion with fiber compression and ensuing axonal damage [25]. In our sample, no difference in hippocampal volume was detected between IDH-wildtype and IDH-mutation glioma patients.…”
Section: Agingmentioning
confidence: 99%
“…Volume loss in brain regions remote to the site of glioma before surgery has also been found using modern imaging methods. For instance, focal glioma in the cerebral cortex leads to volumetric and diffusion alterations in distant subcortical areas, such as the caudate nucleus, putamen, and thalamus, as well as microstructural impairment of extratumoral whole-brain normal-appearing white matter [25,26]. Recently, one study reported that the hippocampus appears to be a brain region that is less prone than other regions to tumor invasion [27].…”
Section: Introductionmentioning
confidence: 99%
“…All participants underwent a standardized cognitive examination, which has been described in more detail previously (Jütten et al, 2019) and included the following tests: The Verbal Learning and Memory Test (VLMT, [Helmstaedter, Lendt, & Lux, 2001]) is a list-learning paradigm, which comprises eight trials with which verbal learning and recall are assessed. Here, we focused on VLMT scores including total learning (the sum of scores for Trials 1-5, VLMT_ P Dg1-5) and consolidation performance as number of words forgotten over time (Trial 5 score-Trial 7 score, VLMT_Dg5-Dg7).…”
Section: Neuropsychological Assessmentmentioning
confidence: 99%
“…All participants underwent MRI examination on a 3T Siemens Prisma MRI scanner equipped with a standard 32-channel head coil. The detailed scanning protocol is described in a previous study (Jütten et al, 2019), and comprised the following pulse sequences: A sagittal 3D T1 magnetization-prepared rapid acquisition gradient echo…”
Section: Mri Data Acquisitionmentioning
confidence: 99%